2020
DOI: 10.1542/peds.2020-1449
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Resuscitation at Birth, Mortality, and Neurodevelopment: A Systematic Review

Abstract: CONTEXT: The International Liaison Committee on Resuscitation Neonatal Life Support Task Force reviewed evidence for the duration of cardiopulmonary resuscitation (CPR) for newborns immediately after birth.OBJECTIVE: To summarize evidence for ongoing CPR on the outcomes of survival, neurodevelopment, and the composite of survival without moderate or severe neurodevelopmental impairment (NDI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 37 publications
0
25
0
1
Order By: Relevance
“…This SysRev identified 15 outcome studies of only 470 newborns. 91 The task force agreed that the limited number of infants in the studies and the heterogeneity of the studies provided very low-certainty evidence on which to base new 2020 treatment recommendations.…”
Section: Impact Of Duration Of Intensive Resuscitationmentioning
confidence: 99%
“…This SysRev identified 15 outcome studies of only 470 newborns. 91 The task force agreed that the limited number of infants in the studies and the heterogeneity of the studies provided very low-certainty evidence on which to base new 2020 treatment recommendations.…”
Section: Impact Of Duration Of Intensive Resuscitationmentioning
confidence: 99%
“…The prevalence of mortality, neurodevelopmental impairment, respiratory support at 28 days, days to full oral feeds and length of stay are very high among the neonates who have received in-birth CPR (8,25). Even the national institute of child health and developmental neonatal research reported that CPR in delivery room is a prognostic factor for morbidity and later complications up to 18 months of age (26).…”
Section: Discussionmentioning
confidence: 99%
“…chest compression with or without injecting epinephrine (7). Many studies have been performed on CPR consequences, and it has been found that mortality, neurological morbidity, neurodevelopmental impairment, lower motor scores and ROP are more prevalent among the preterm infants who have received CPR (6,8,9). Thus, timely identi cation and rapid CPR of neonates in the delivery room can reduce the neonatal mortality and morbidity (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bei extremen Frühgeborenen sind längere Reanimationen mit geringeren Überlebensraten und einer höheren Morbidität verbunden. Die Entscheidung zum Abbruch einer Reanimation soll hier individuell getroffen werden [ 371 , 372 ].…”
Section: Wissenschaftliche Grundlagen Auf Deren Basis Die Empfehlungen Für Die Praxis Zur Versorgung Und Reanimation Des Neugeborenen Berunclassified